A Man and the World: the poetic anthropology of K. Kavafis and G. Seferis - Савенко, Андрій Олександрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article is an attempt to analyze the poetry of two famous Greek poets, K.Kavafis and G.Seferis as anthropological projects whose textual space is designed to present two different types of human cognition with regard to history and cultural tradition. Being a peculiar incarnation of cultural and social histories, a MAN appears as a person in progress in Kavafis’ poetry; hence the author’s tendency to picture a human experience as an open coordinate system. An important principle unifying the poetry of K. Kavafis, which arises from the principled fragmentation of his poetic world, can be formulated as follows: the essence of a person always has a potential dimension, part of our nature, which manifests itself in the current situation, is oriented towards the future and such an orientation has an ontological status. A person has a unique openness to the world and it causes the poet's main attention. First of all, because such openness in the transition from the world of nature to the world of society becomes the object of claims, produced by different institutions created by man, but at the same time, that control him, often depriving him of the right to be himself, attempting on his bodily completeness and spiritual integrity. Kavafis’ poetry with the help of a complex structure of artistic time and the art of hinting creates a mechanism for "re-opening a person"-in progress. We can suggest that Kavafis constructs his hero’s image in a photographic manner, where the historical figures, circumstances, actions and generally the whole historical knowledge as a discourse prepare the frame for poetic camera to make a 3-D picture that binds contemporary mode of reader’s existence with panchronic dimension of the text. On the contrary, the poetics of G.Seferis, who was both Kavafis’ literary competitor and artistic heir, suggests a concept of a MAN as a closed and strictly determined system that can evolve only if the law of excluded middle is applied; therefore, in terms of a human being’s actions and experiences, its intent is on a predefined axiological model. Poet's aim in the anthropological sense is not so much the creation or change of the potential identities of man, but rather the search for certain unchangeable principles that constitute the essence of human existence, but are outside the person himself. At different stages of the poet's work this principle can be presented as: the Greeks as a cultural community; Greece as the materialization of ethical principles; the soul as an immortal part of a person, creating its integrity and immutability, counteracting its body as unstable and unstable. As in a movie, persona of Seferis’ poetry acts like an actor in accordance with the instructions taken from the movie director that turns our views from the hero himself to the author’s intentions which explains the effect of masking the heroes using often by G. Seferis.